Implementasi Peraturan Gubernur Daerah Istimewa Yogyakarta Nomor 60 Tahun 2020 dalam Pembelajaran Pendidikan Pancasila dan Kewarganegaraan - Sumaryati, Sumaryati; Merkuri, Yulia Gesti (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2023)
This study aimed to analyze the insertion of anticorruption education, the realization of anti-corruption values, and the obstacles to inserting anti-corruption education in learning Pancasila and Civic Education. This study combined qualitative and quantitative approaches with a case study type. The results of the study showed that the inclusion of anti-corruption education in learning was carried out through four stages, namely identifying essential competencies, learning achievement indicators, and anti-corruption education materials; inserting anti-corruption education materials into essential competencies and learning achievement indicators; determining the methods, media, and evaluation of learning; as well as carrying out learning that contained anti-corruption educational material. The anti-corruption values students realize in learning include honesty, caring, independence, discipline, responsibility, hard work, simplicity, courage, and fairness. The obstacles to inserting anti-corruption education into learning were teachers experiencing difficulties developing strategies, choosing methods, and developing appropriate materials and media